2017
DOI: 10.1073/pnas.1611506114
|View full text |Cite
|
Sign up to set email alerts
|

Entropic forces drive self-organization and membrane fusion by SNARE proteins

Abstract: SNARE proteins are the core of the cell's fusion machinery and mediate virtually all known intracellular membrane fusion reactions on which exocytosis and trafficking depend. Fusion is catalyzed when vesicle-associated v-SNAREs form trans-SNARE complexes ("SNAREpins") with target membrane-associated t-SNAREs, a zippering-like process releasing ∼65 kT per SNAREpin. Fusion requires several SNAREpins, but how they cooperate is unknown and reports of the number required vary widely. To capture the collective behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
82
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 53 publications
8
82
1
Order By: Relevance
“…Here we addressed this challenge by developing a molecular dynamics description with SNAREs systematically but radically coarse‐grained, to such a degree that we could simulate the collective behavior of up to 20 SNAREpins on timescales up to ~100 μs. The results are consistent with our earlier study of the long time equilibrated behavior of the SNAREpins using a Monte Carlo approach which can only describe equilibrium . There we estimated fusion times using a scaling argument for the timescales and by fitting to an in vitro measurement of fusion time .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Here we addressed this challenge by developing a molecular dynamics description with SNAREs systematically but radically coarse‐grained, to such a degree that we could simulate the collective behavior of up to 20 SNAREpins on timescales up to ~100 μs. The results are consistent with our earlier study of the long time equilibrated behavior of the SNAREpins using a Monte Carlo approach which can only describe equilibrium . There we estimated fusion times using a scaling argument for the timescales and by fitting to an in vitro measurement of fusion time .…”
Section: Discussionsupporting
confidence: 89%
“…), consistent with the large spread in reported SNARE requirements for fusion . Given that any number can catalyze fusion, different apparent requirements may emerge from different experimental methods depending on the timescale probed . Further, these conclusions suggest that, in the interests of efficiency, the number of SNAREpins used at synaptic terminals to achieve membrane fusion may equal the minimum number required to achieve the sub‐millisecond timescales necessary for proper neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, zippering of several nearby SNARE complexes likely leads to formation of a ring‐shaped arrangement followed by entropically driven radial expansion. This expansion will pull the membranes together with high force depending on the number of SNARE complexes . Given the increased distance between the SNARE complexes, this will likely produce a hemifused zone as observed in the experiments described above.…”
Section: Do Hemifusion Intermediates Exist?mentioning
confidence: 94%
“…At least three copies of SNAP25 appear to be required for fast fusion in chromaffin cells . It has been suggested that the fusion rate may increase with increasing numbers of SNARE complexes and that activation of fusion within 1 ms may require a cluster of at least 15 SNARE complexes . These results suggest that fusion pores may be formed by a variable number of SNARE complexes leading to fusion pore properties that depend on this number.…”
Section: Fusion Pore Conductance and Fusion Pore Structurementioning
confidence: 99%